VNU journal of social sciences and humanities (University of social sciences and humanities, 2016)
Contents: Prevention strategies andmental health in Vietnam. Moderators of the effectiveness of multisystemic therapy outcome for adolescents with severe conduct problems. Introduction of KSAP technique survey into community-based tourism study: Case study in Na Hang, Tuyen Quang province. On the earliest version of the Miaoshan-Guanyin story in Vietnam: Ad adaption of a Chinese narrative in the Nom script. In search of the scientific basis for teacher preparation. Management challenges of spontaeous settlements in Ho Chi Minh city, Vietnam: A case study at Thoi Tam Thon country,...